2006
DOI: 10.1007/s10750-005-1014-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Isomorphic Cold-Water Dinoflagellates (Scrippsiella/Woloszynskia Complex) Causing ‘red tides’ in the Baltic Sea

Abstract: During the latest years medium-sized (15-30 lm), single-celled dinoflagellates have been reported to form blooms in the northern Baltic Proper and the Gulf of Finland in winter and spring. Recent studies (Kremp et al., 2003. Proceedings of the 7th International conference of Modern and Fossil Dinoflagellates, September 21-25, Nagasaki, Japan, 66 pp.) indicate that those blooms are caused by two isomorphic species -Scrippsiella hangoei (Schiller) Larsen, and a new species, tentatively belonging to the genus Wol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The spring bloom field study revealed higher cell concentrations of B. baltica at Längden (~22 000 cells l -1 ), the offshore sampling station, compared to the inshore station Storfjärden (~10 000 cells l -1 ). Jaanus et al (2006) found that the Scrippsiella/Woloszynskia complex occurred at lower concentrations in coastal areas that are influenced by freshwater inflows. As the salinity differences between the stations in our study were minor (less than 0.5), the difference in abundance might be due to other factors.…”
Section: Biecheleria Baltica Bloom Dynamics As Revealed By Fishmentioning
confidence: 99%
“…The spring bloom field study revealed higher cell concentrations of B. baltica at Längden (~22 000 cells l -1 ), the offshore sampling station, compared to the inshore station Storfjärden (~10 000 cells l -1 ). Jaanus et al (2006) found that the Scrippsiella/Woloszynskia complex occurred at lower concentrations in coastal areas that are influenced by freshwater inflows. As the salinity differences between the stations in our study were minor (less than 0.5), the difference in abundance might be due to other factors.…”
Section: Biecheleria Baltica Bloom Dynamics As Revealed By Fishmentioning
confidence: 99%
“…The phytoplankton community during the highly productive spring is dominated by diatoms and dinoflagellates in most of the Baltic Sea (Niemi, 1975;Heiskanen, 1993;Wasmund et al, 1998;Höglander et al, 2004;Tamelander and Heiskanen, 2004;Jaanus et al, 2006). Diatoms are generally very successful during periods of high new production (i.e., production based on accumulated nitrate), like the spring bloom, as their higher growth rate enables them to outcompete e.g., dinoflagellates (Reynolds, 2006).…”
Section: Changing Phytoplankton Communitymentioning
confidence: 99%
“…10 000 cells ml , which corresponds to bloom conditions in the field (e.g. Heiskanen 1993, Larsen et al 1995, Jaanus et al 2006, Spilling 2007. Starting concentrations of the target species were ca.…”
Section: Experimental Designmentioning
confidence: 99%